ESTABLISHING GENETIC PARAMETERS BLACK POD DISEASE FOR SOME OF ACEH’S ORIGIN GENOTIPE COCOA (Theobroma cacao L.) - Rahayu Eka Sari; Siti Hafsah; Nurhayati Nurhayati; Firdaus Firdaus (UNEJ e-Proceeding, 2017)
Research of prediction parameter genetics in cacao plants at the nursery fase important asinformation on cacao plants that is resistant to attack Phytoptora palmivora and cancharacterized of morphology of that plants. The goal of this research is to know the value ofthought of the parameters of genetics on growth and resistance characters to black poddisease for some of Aceh’s origin genotypes. The research is done in two packages, namelythe growth and resistance plants packages. Design used are thought of random complete(ral)with ten genotypes as treatments and repeated as many as three times. Variables enduranceare qualitative variable (the form of stem of plant, a leaf shape, form the base of a leaf, theform of leaf tips, and flush color) quantitative variable (high plants, long leaves, number ofleaves per stem, wide leaves, and the angle between the leaves with stem), and resistancevariable (the incubation, the percentage of disease, and severity of illness). The result showthat: genotype categorized somewhat endurance element is AT7 and SR45.